Shepherin II Gene Synthesis and Peptide Characterization: E. coli Expression, Purification, and Antiviral Activity - Elfattah, Azza Abd; Samir, Safia; Okasha, Hend; Atef, Azza Ahmed; Taha, Alshaimaa (Protein and Peptide Letters, 2025)
IntroductionThe shepherin II peptide is characterized by a histidine/glycine-rich sequence. This study aimed to design, express recombinantly, and evaluate the antiviral activity of shepherin II against hepatitis A virus (HAV).MethodsThe shepherin II gene was reverse-translated, cloned into the pET-3a vector, and expressed in E. coli BL21 (DE3) pLysS cells induced with 2 mM IPTG. Purification was achieved via cation exchange chromatography, and intact mass analysis using mass spectrometry was carried out. Cytotoxicity on normal Vero cells and antiviral activity on HAV were evaluated.ResultsThe mass spectrometry confirmed a primary peptide fragment with a molecular weight of 3,421.30 Da (100% relative abundance). SDS-PAGE verified peptide expression. Cytotoxicity tests on Vero cells showed a CC50 of 219.26 ± 7.91 µg/ml. Antiviral assay revealed an EC50 of 113.92 ± 4.58 µg/ml against HAV, resulting in a selectivity index (SI) of 1.92. This SI indicates limited selectivity compared to the reference drug amantadine, which exhibited an EC50 of 5.67 ± 0.71 µg/ml and an SI of 53.41.DiscussionThe recombinant expression of shepherin II was successfully achieved and confirmed by mass spectrometry and SDS-PAGE. The peptide showed measurable antiviral activity against HAV.ConclusionThis study demonstrated the feasibility of recombinant shepherin II production and assessed its antiviral activity. However, the limited selectivity index of shepherin II remains a challenge that needs to be addressed through molecular modification or alternative delivery strategies to improve its clinical potential.
Keywords: Histidine-glycine rich peptide